Globalization and environmental policy innovations: Perspectives for national and regional pioneers - Martin Jaenicke (European Regional Science Association (ERSA), 1998)
Is economic globalisation an obstacle to environmental policy innovations of regions or nations? Which effects will the rapid globalisation of environmental policy have? Could globalisation improve the conditions for regulatory competition and green pioneers? The presentation will describe the growing environmental policy convergence in the world, which may prevent a downward spiral of environmental standards. Global environmental policy learning will be described in terms of environmental policy diffusion between countries and regions. The perspective for environmental pioneers may be better than before!
Keywords: 330